Proceedings of the First Workshop on Online Social Networks 2008
DOI: 10.1145/1397735.1397751
|View full text |Cite
|
Sign up to set email alerts
|

Are you moved by your social network application?

Abstract: This paper studies a Bluetooth-based mobile social network application deployed among a group of 28 participants collected during a computer communication conference. We compare the social graph containing friends, as defined by participants, to the contact graph, that is the temporal network created by opportunistic contacts as owners of devices move and come into communication range. Our contribution is twofold: first, we prove that most properties of nodes, links, and paths correlate among the social and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 10 publications
(13 reference statements)
1
38
0
Order By: Relevance
“…Spatio-temporal aspects have also been studied for the analysis of delay and data delivery in DTN networks [7,3]. The Kempe-Kleinberg model has also been adapted for social networks analysis [5,13,1], however the focus of these works is on the local characteristics of time-varying networks; global aspects of the information processes in these networks are not captured.…”
Section: Introductionmentioning
confidence: 99%
“…Spatio-temporal aspects have also been studied for the analysis of delay and data delivery in DTN networks [7,3]. The Kempe-Kleinberg model has also been adapted for social networks analysis [5,13,1], however the focus of these works is on the local characteristics of time-varying networks; global aspects of the information processes in these networks are not captured.…”
Section: Introductionmentioning
confidence: 99%
“…However, as real and large-scale traces of human mobility started to be collected, scientists demonstrated that human movement is not random at all (e.g., [18,19,20,21]); rather, it can be predicted to a large extent (e.g., [22,23]). A new generation of DTN protocols has then been proposed, that reasons upon human mobility patterns, in a quest to better trade delivery with overhead (e.g., [1,24,25,7]). Whilst largely successful in attaining this goal, all DTN routing protocols heavily rely on the voluntary participation of nodes in the network to forward content.…”
Section: Motivationmentioning
confidence: 99%
“…Routing algorithms can benefit by incorporating this additional information. It has been shown that forwarding messages through social neighbours can achieve better delivery performance in a small conference environment than random forwarding [34].…”
Section: Peoplerank Routingmentioning
confidence: 99%